NUMERICAL SIMULATION OF REINFORCED CONCRETE SHEAR WALL USING 3D-NLFEA - Ainun Najib; Bambang Piscesa; Harun Alrasyid (Institut Teknologi Sepuluh Nopember (ITS), 2022)
This paper present a numerical simulation of a reinforced concrete shear wall loaded under in-plane and out-of-plane directions using a 3D-NLFEA finite element package. The applied vertical load is controlled as a fraction of the horizontal in plane load. Therefore, inside the 3D-NLFEA package, a special routine was developed to account for changes in the vertical load as a function of the lateral load. The performance of the numerical model is evaluated by comparing not only the load deformation response but also the normalized average strain along the length and height of the shear wall. This study found that the predicted peak and ultimate load only differ by about 0.5% and 0.4%, respectively. By observing the location where the normalized average strain is zero, the average compressive stress from the numerical model can be back-calculated and is 39.73 MPa which is higher than the unconfined concrete compressive strength due to confinement to the core by the tie in the boundary element. On the other hand, the back-calculated average compressive stress from the test result is 26.11 MPa which is lower than the unconfined concrete compressive strength. Therefore, it can be concluded that the proposed numerical model for predicting the shear behavior loaded under in-plane and out-of-plane directions were found to be reasonable and satisfactory.